UPAYA MEWUJUDKAN WISATA ALAM DAN KULINER DI DESA BINANGUN SERANG - Tia Fitria Saumi; Raden Irna Afriani; Rendi Rendi; Sopiyatul Jamilah (Indonesian Collaboration Journal of Community Services, 2021)
The tourism sector is a new style industry that can revive other, especially the economic sector for the surrounding community. Tourist visits to an area can create new job vacancy for the local communities and increase the regional cash income. The most popular tourist attraction today is nature tourism. The prolonged COVID-19 pandemic condition makes people bored at home and looking for alternative natural tourism to relieve fatigue and refresh the mind. One of the villages that has recently been visited by many people is Binangun Village. The location of this village is quite strategic because it is located in Waringin Kurung District, which is the border between Serang Regency and Cilegon City. The area is still beautiful and there are many trees with the contours of the road going up and down, making this area a popular area for visitors, especially the bicycle community. In addition, this village has a famous culinary specialty, namely the Cibangkong lupis cake. Community service activities carried out in this village aim to develop the potential of the village from environmental management to local Micro, Small, and Medium Enterprises (MSMEs), so that this village is more widely known in the community as a village that offers natural tourism and culinary